A pilot study on ecological momentary assessment in asylum-seeking children and adolescents resettled to Germany: Investigating compliance, post-migration factors, and the relation between daily mood, sleep patterns, and mental health. - Lauritz Rudolf Floribert Müller; Katharina Gossmann; Regina F Schmid; Rita Rosner; Johanna Unterhitzenberger (PLoS ONE, 2021)
Background Asylum-seeking children and adolescents (ASCs) resettled to western countries show elevated levels of psychological distress. While research on the mental health of ASCs is increasing, less is known about their day-to-day living experiences such as their daily mood, sleep patterns, and post-migration factors. Moreover, no examination in situ, using smartphone-assisted ecological momentary assessment (EMA), has been conducted up to now among ASCs. Furthermore, we do not know if screening measures succeed in reflecting the daily mood of ASCs experienced in everyday life. Methods We undertook a smartphone-assisted EMA study over a two-week period with 3 measurements a day. Participants were N = 40 ASCs from 10 different countries who had resettled to Germany. They completed standardized questionnaires screening for history of trauma and clinical symptoms (post-traumatic stress symptoms, depression, and anxiety) that were carried out in interview-like settings, and they participated in the subsequent EMA where they rated mood, sleep parameters, and post-migration factors on a daily basis. Multilevel models of clinical symptoms, daily mood, and sleep parameters were computed based on a total of 680 measurements. Results The multiply traumatized and highly distressed participants reported different levels of discrimination, and various social activities and contacts in the EMA. The overall compliance rate was shown to be 40.5%. Higher PTSS and anxiety scores were associated with lower levels of daily mood and poorer outcomes of some sleep parameters. Depression scores were not associated with any of the variables assessed in the EMA. Conclusions Smartphone-assisted EMA among ASCs resettled to Germany proved to be implementable despite a rather low compliance rate. Not only do ASCs show high symptom levels, they are also affected by these symptoms in their daily lives. The results emphasize the need for concise screenings and psychological treatment for this high-risk population. Limitations include the convenient nature of the sample and the lack of a comparison group.